ANALYSIS OF FINANCIAL PERFORMANCE REGIONAL EXPENDITURES BUDGET (APBD) OF WEST NUSA TENGGARA (NTB) PROVINCE 2017-2019 - Zilvi Irta Rizkita; Santi Padilawati; Siskawati; Tena Patrasia; Yazid Bustaomi (Journal of Finance, Economics and Business, 2022)
The purpose of this research is to find out the result of an analysis of the financial performance of the province of West Nusa Tenggara (NTB) for the 2017-2019 period which was allocated usingthe clculation of ratios from the Regional Revenue and Expenditure Budget (APBD) data. The results of the research show that the ratio of financial performance is empirically proven to financial performance is emoirically proven allocate the of autonomy Regional Expenditure (APBD) and the relationship between the regional financial balance fund and the study relationship.The effect of decentralization of regional autonomy on comsuntion has not been proven empirically.